2023
DOI: 10.3390/agronomy13030861
|View full text |Cite
|
Sign up to set email alerts
|

Energy Crisis—Alternative Use of Winter Bread Wheat Grain Depending on Protein Content

Abstract: Our economic analysis aimed to evaluate the profitability of winter bread wheat production based on two fundamental aspects. The first was the grainprotein content as a criterion for determining grain prices. The other was a comparative simulation of production profitability relying on grain production costs in 2015 and 2022. We used the results of a field experiment conducted in 2014 and 2015 involving winter bread wheat fertilised with nitrogen applied at progressive increments of 40 kg N ha−1 within arange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These two production goals are consistent with the primary goal of classical farming practice, as their implementation focuses primarily on protein yield. Moreover, these objectives also align with the main economic objective of the farmer, as they boost the economic effect [15].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These two production goals are consistent with the primary goal of classical farming practice, as their implementation focuses primarily on protein yield. Moreover, these objectives also align with the main economic objective of the farmer, as they boost the economic effect [15].…”
Section: Introductionmentioning
confidence: 90%
“…A CP content of 12.5-13% and GL of 25-28% meet the technological quality of grain for bread wheat [22]. High N f concentrations are applied during the CCW to increase the CP content in the grain [14,15]. Tissue analysis of winter wheat to determine the plant N status is only used to determine the need for N f application during the booting or heading stage of cereal plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…The standardized protein content in high-quality flour is determined by both the wheat variety and the appropriate dose of N f applied [9]. The study presented in the paper by Klikocka and Szczepaniak [10] clearly showed that the production of winter bread wheat, taking into account both the grain yield and its quality, is profitable providing a high dose of N f and full fungicide protection. On the fungicide-protected variant, a grain yield of 12.3 t ha −1 was achieved with an optimal N f of 231 kg N ha −1 .…”
Section: High-and Low-input Strategies For Different Winter Wheat Pro...mentioning
confidence: 99%
“…In the presented case, production losses concern both grain (−2.8 t ha −1 , i.e., 23%) and protein content (−3 p.ps.) [10]. Replacing organic fungicides with inorganic ones, considering the pressure of pathogens on the growth and yield of winter wheat, is a major challenge for both researcher and farmers.…”
Section: High-and Low-input Strategies For Different Winter Wheat Pro...mentioning
confidence: 99%
See 1 more Smart Citation